2014
DOI: 10.1063/1.4895494
|View full text |Cite
|
Sign up to set email alerts
|

High temperature optical absorption edge of CdTe single crystal

Abstract: The optical absorption edge of bulk CdTe single crystal was measured by infrared transmission under saturated Cd pressure in the temperature interval 295–1223 K. The absorption coefficient was directly determined up to the value of 100 cm−1. For higher values, it was estimated by extrapolating the spectra according to the Urbach exponential rule. It was observed that the common temperature-independent intersection of extrapolated Urbach absorption edge, the “Urbach focus,” does not exist in CdTe. The temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…[23] one can expect the value of barrier height of the n-type CdTe/Au T = 129°C around 0.78 eV. Adding this value for n-type to our value 0.71 eV retrieved for p-type CdTe, we obtain the value of 1.49 eV at 402 K. This fits with the reported value of CdTe bandgap [24,25] at this temperature.…”
Section: Materials and Experimental Techniquesupporting
confidence: 81%
“…[23] one can expect the value of barrier height of the n-type CdTe/Au T = 129°C around 0.78 eV. Adding this value for n-type to our value 0.71 eV retrieved for p-type CdTe, we obtain the value of 1.49 eV at 402 K. This fits with the reported value of CdTe bandgap [24,25] at this temperature.…”
Section: Materials and Experimental Techniquesupporting
confidence: 81%
“…This comparison suggests that voltage losses due to band tails and other electronic effects that affect the bandgap are less than 47 mV. In single‐crystal CdTe, band tails are ≈10 mV, but tails are larger in group‐V‐doped CdSeTe solar cells…”
mentioning
confidence: 95%
“…They also note that the primary AOS and transparent conducting oxide candidates based on In 2 O 3 , ZnO, and SnO 2 already have remarkably small effective masses, and therefore, it is unlikely to find an oxide with a significantly smaller effective mass. It has been reported that perfect, defect‐free single‐crystal semiconductors have an Urbach energy on the order of 5–10 meV caused by thermal disorder in the lattice . Hence, our lower estimate of 10 meV for W TA is based on the fact that even if compositional and spatial disorder are extraordinarily small, thermal disorder will yield a non‐negligible band tail slope.…”
Section: Amorphous Semiconductor Mobility Limitsmentioning
confidence: 77%
“…It has been reported that perfect, defect-free single-crystal semiconductors have an Urbach energy on the order of 5-10 meV caused by thermal disorder in the lattice. [24][25][26] Hence, our lower estimate of 10 meV for W TA is based on the fact that even if compositional and spatial disorder are extraordinarily small, thermal disorder will yield a non-negligible band tail slope. Values for N TA are difficult to obtain experimentally and as a result are rarely reported.…”
Section: Summary Of Transport Model Equationsmentioning
confidence: 90%